Re-Design and Development of Cirebon City MSME Digital Promotion Media as Implementation of Project-Based Learning MBKM Consultation Project - Prawira, Nanang Ganda; Hikmatyar, Aditya Aditama Putri; Ramadhani, Fathia Salma (VCD, 2024)
The lack of visual branding and visual promotion development has resulted in MSMEs in Cirebon City experiencing stagnation in business. Based on interviews and initial observations on several samples of Cirebon City MSMEs, branding re-design, packaging re-design, and digital promotion development are needed. As a partner of the Cirebon City Government, the UPI Visual Communication Design Study Program has become a Design Consultant Team to develop and strengthen the visual promotion of MSMEs through monitoring Consultancy Project lectures. Research and design development methods are carried out using design thinking. This research uses the design thinking method to present the visual branding of two MSMEs. Starting from understanding the needs of MSMEs (empathy), identifying problems (define), solutions through academic ideas or conceptual ideas (ideate), visual solutions (prototype), and trials (test). The research output is a selected design that will be presented and exhibited to the public, especially MSME clients in Cirebon City. Implementing the MBKM program has significantly influenced the skills of Visual Communication Design, Faculty of Arts and Design Education, Universitas Pendidikan Indonesia’s students, including improving critical and creative thinking skills, training leadership skills, and collaboration skills, fostering a good work ethic and culture, and forming professionalism in students.